2006
DOI: 10.1590/s0103-64402006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Sealer penetration and marginal permeability after apicoectomy varying retrocavity preparation and retrofilling material

Abstract: Apicoectomy failure is generally related to inappropriate marginal sealing of the retrocavity, which allows percolation of microorganisms and their products from root canal system to periapex. This study evaluated tubular penetration of canal sealers and marginal permeability after retrocavity irradiation with Er;Cr:YSGG laser and retrofilling with MTA or cyanoacrylate. Twenty-two singlerooted teeth were decoronated and endodontically treated, their apical 3 mm were resected and the root ends were retroprepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 16 publications
0
19
0
11
Order By: Relevance
“…Adesivos à base de cianoacrilato têm sido bastante utilizados nas diversas áreas da Medicina e da Odontologia [20]. Alguns estudos têm mostrado o uso do cianoacrilato como adesivos cirúrgicos [19,21,22], durante terapia endodôntica [23,24] e para estabilização do lençol de borracha durante isolamento absoluto [25]. Os resultados clínicos e histológicos destes estudos têm demonstrado a baixa toxicidade desse material.…”
Section: Discussionunclassified
“…Adesivos à base de cianoacrilato têm sido bastante utilizados nas diversas áreas da Medicina e da Odontologia [20]. Alguns estudos têm mostrado o uso do cianoacrilato como adesivos cirúrgicos [19,21,22], durante terapia endodôntica [23,24] e para estabilização do lençol de borracha durante isolamento absoluto [25]. Os resultados clínicos e histológicos destes estudos têm demonstrado a baixa toxicidade desse material.…”
Section: Discussionunclassified
“…Karlovic et al 7) and Kocak et al 21) showed that MTA-filled root-end cavities prepared by Er:YAG laser had significantly lower microleakage than those prepared using ultrasonic devices. However, in the absence of smear layers, there seemed to be no apparent advantages in the use of Er,Cr:YSGG laser over conventional root-end cavity preparation methods to address apical microleakage of root-end fillings 22,23) . In agreement with the results of these studies, Er,Cr:YSGG laser treatment did not influence the sealing ability of the root-end filling materials tested in this study when compared with EDTA application.…”
Section: Discussionmentioning
confidence: 99%
“…36 Apicectomy failure is generally related to inappropri ate marginal sealing of the retro-cavity, which allows percolation of micro-organ isms and their products from the root canal system into the peri-apical tissue. 37 The majority of periapical lesions har bour a variety of flora which cannot be eradicated despite a thorough apicec tomy procedure. 38 Surgical re-treatment of teeth previously treated with surgery is a valid alternative to extraction.…”
Section: Discussionmentioning
confidence: 99%